Naxi Cosmology of Mt Yulong Sacred Sites with Caveats for Conservation - Jan Salick; Robbie Hart; Li Siyu (Revue d'ethnoécologie)
Mt Yulong is central to Naxi people of Southwest China. Through participatory mapping, free listing, and extended semi-structured interviews, we explored relations of Naxi cosmologies of sacred space with “biodiversity conservation”. For this commonly espoused partnership, we found encouragement, skepticism and challenges. Naxi perspectives on sacred space and conservation ranged in scale from hyper-local, through regional, to historical and cosmological. Some participants worried about conjoining religion with government conservation initiatives. Others argued conceptually that “conservation” prioritizes people while traditional Naxi cosmology stresses equality and brotherhood between people and nature. Challenges for conservation would be to integrate this cosmological view as well as origin myths, Naxi traditions of suicide, and Sanduo, the god of Mt Yulong, who “shines like lightning [and his] mouth spits fire” – not a deity to be engaged without care. Naxi stressed primacy of culture and cosmology. These cosmological issues raised in a local context are of far greater magnitude than one culture and one mountain and may suggest paths to effective conservation of sacred natural spaces around the world.